2007
DOI: 10.1186/1471-2458-7-153
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HIV infection in Males who have Sex with Males (MSM) in Bangladesh

Abstract: Background: Recent surveillance data from Bangladesh indicate rising HIV infection among intravenous drug users (IDU) in the country. We suggest a likely association between HIV risk factors in this group and other groups, such as males who have sex with males (MSM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…This is higher, yet somewhat comparable, to the 18% figure found in a 2006 survey of PWID in Delhi (Sarna et al, 2012). Surveys in Iran (11.3%) (Zamani et al, 2010), Brazil (26.4%) (Ferreira et al, 2006), Bangladesh (10%) (Chan & Khan, 2007) and Afghanistan (25.7%) (Todd et al, 2010) have similarly found a high proportion of male PWID who have a history of sex with men. Haque et al (2004) surveyed male PWID across multiple sites in Pakistan and found that 13% exclusively had sex with males and 30% had sex with both males and females in their lifetime.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is higher, yet somewhat comparable, to the 18% figure found in a 2006 survey of PWID in Delhi (Sarna et al, 2012). Surveys in Iran (11.3%) (Zamani et al, 2010), Brazil (26.4%) (Ferreira et al, 2006), Bangladesh (10%) (Chan & Khan, 2007) and Afghanistan (25.7%) (Todd et al, 2010) have similarly found a high proportion of male PWID who have a history of sex with men. Haque et al (2004) surveyed male PWID across multiple sites in Pakistan and found that 13% exclusively had sex with males and 30% had sex with both males and females in their lifetime.…”
Section: Discussionmentioning
confidence: 73%
“…Research elsewhere has identified sizeable sub-populations for whom injecting drug use overlaps with male-to-male sex (Chan & Khan, 2007;Ferreira, Caiaffa, Bastos, Mingoti, & Projeto, 2006;Haque et al, 2004;Johnston et al, 2010;Kral et al, 2005;Parviz et al, 2006;Strathdee & Sherman, 2003;Todd et al, 2010;Zamani et al, 2010). Men who both inject drugs and have sex with men are particularly vulnerable to HIV infection and have the potential to transmit the virus across multiple populations.…”
Section: Introductionmentioning
confidence: 96%
“…16,17 Many studies have investigated the factors associated with unprotected sexual behaviors. 18,19 However, due to inadequate research methods, the literature on the relationship between risk factors and high-risk sexual behaviors in MSM is limited. Since the 1960s and 1970s, structural equation modeling (SEM) has been a statistical analysis method that represents one of the three major advances in the field of statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Although, awareness in males are high [16] but the prevalence among them is high compared to females. This may be by the cause that males are three times more vulnerable to transmission of this epidemic than females [17]. Among the males who sex with males and also exposed to anal sex are more vulnerable to spread of this pandemic, which facilitate the spread of HIV virus in very easy way [18,19,20].…”
Section: Resultsmentioning
confidence: 99%